2017
DOI: 10.1096/fj.201601032r
|View full text |Cite
|
Sign up to set email alerts
|

Gestational disruptions in metabolic rhythmicity of the liver, muscle, and placenta affect fetal size

Abstract: Maternal metabolic adaptations are essential for successful pregnancy outcomes. We investigated how metabolic gestational processes are coordinated, whether there is a functional link with internal clocks, and whether disruptions are related to metabolic abnormalities in pregnancy, by studying day/night metabolic pathways in murine models and samples from pregnant women with normally grown and large-for-gestational age infants. In early mouse pregnancy, expression of hepatic lipogenic genes was up-regulated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 58 publications
(75 reference statements)
2
13
1
Order By: Relevance
“…This study, which is consistent with other recent studies, showed that female Bmal1 −/− mice were infertile [98]. Bmal1 −/− mice had lower levels of fertilization, Bmal1 −/− mice obtained blastocyst numbers compared with that of WT mice after superovulation and being mated with WT males [98]. Additionally, Mereness et al reported that the deletion of Bmal1 had locus in ovarian granulosa cells (GCs) (Granulosa Cell Bmal1 KO; GCKO) or theca cells (TCs) (Theca Cell Bmal1 KO; TCKO) [99].…”
Section: Bmal1supporting
confidence: 94%
See 2 more Smart Citations
“…This study, which is consistent with other recent studies, showed that female Bmal1 −/− mice were infertile [98]. Bmal1 −/− mice had lower levels of fertilization, Bmal1 −/− mice obtained blastocyst numbers compared with that of WT mice after superovulation and being mated with WT males [98]. Additionally, Mereness et al reported that the deletion of Bmal1 had locus in ovarian granulosa cells (GCs) (Granulosa Cell Bmal1 KO; GCKO) or theca cells (TCs) (Theca Cell Bmal1 KO; TCKO) [99].…”
Section: Bmal1supporting
confidence: 94%
“…They found significantly lower levels of fertilization and obtained blastocyst numbers in Bmal1 −/− mice compared with that in Bmal1 +/+ mice, after superovulation and being mated with wild-type males [97]. This study, which is consistent with other recent studies, showed that female Bmal1 −/− mice were infertile [98]. Bmal1 −/− mice had lower levels of fertilization, Bmal1 −/− mice obtained blastocyst numbers compared with that of WT mice after superovulation and being mated with WT males [98].…”
Section: Bmal1supporting
confidence: 91%
See 1 more Smart Citation
“…Mice were sacrificed on day 0 or day 18 of pregnancy, resulting in n = 6‐8 per group. Separate cohorts of C57BL/6 mice were sacrificed at increasing gestational ages (days 2, 7, 10, 14, and 18; n = 6‐7 per time point), as described …”
Section: Methodsmentioning
confidence: 99%
“…Thus, even though the exact mechanisms are not known, the current data indicates the likely importance of maternal circadian signals such as melatonin, in driving rhythmic placental function (Chuffa et al 2019). In addition, the raised triglyceride levels observed in human placentas from pregnancies with large-for-gestational age infants are found to be associated with upregulated expression of the clock gene BMAL1 (Papacleovoulou et al 2017). Ohhashi and colleagues investigated 115 cases of placental abruption retrospectively and reported that abdominal pain and adverse perinatal outcomes including perinatal death showed significant circadian variation (Ohhashi et al 2017).…”
Section: Authors Animals or Subjects Major Implicationsmentioning
confidence: 76%